Sarcoidosis-Associated Pulmonary Hypertension - Huitema, Marloes P.; Mathijssen, Harold; Mager, Johannes J.; Snijder, Repke J.; Grutters, Jan C.; Post, Marco C. (Seminars in Respiratory and Critical Care Medicine, 2020)
Pulmonary hypertension (PH) is a well-known complication of sarcoidosis, defined by a mean pulmonary artery pressure of ≥25 mm Hg. Since both PH and sarcoidosis are rare diseases, data on sarcoidosis-associated PH (SAPH) is retrieved mostly from small retrospective studies. Estimated prevalence of SAPH ranges from 3% in patients referred to a tertiary center up to 79% in patients awaiting lung transplant. Most patients with SAPH show advanced parenchymal disease as the underlying mechanism. However, some patients have disproportional elevated pulmonary artery pressure, and PH can occur in sarcoidosis patients without parenchymal disease. Other mechanisms such as vascular disease, pulmonary embolisms, postcapillary PH, extrinsic compression, and other sarcoidosis-related comorbidities might contribute to SAPH. The diagnosis of PH in sarcoidosis is challenging since symptoms and signs overlap. Suspicion can be raised based on symptoms or tests, such as pulmonary function tests, laboratory findings, electrocardiography, or chest CT. PH screening mainly relies on transthoracic echocardiography. Right heart catheterization should be considered on a case-by-case basis in patients with clinical suspicion of PH, taking into account clinical consequences. Treatment options are considered on patient level in a PH expert center, and might include oxygen therapy, immunosuppressive, or PH-specific therapy. However, qualitative evidence is scarce. Furthermore, in a subset of patients, interventional therapy or eventually lung transplant can be considered. SAPH is associated with high morbidity. Mortality is higher in sarcoidosis patients with PH compared with those without PH, and increases in patients with more advanced stages of sarcoidosis and/or PH.
Keywords: pulmonary hypertension; sarcoidosis; sarcoidosis-associated pulmonary hypertension